2021
DOI: 10.1002/eji.202048757
|View full text |Cite
|
Sign up to set email alerts
|

Development of Plasmodium‐specific liver‐resident memory CD8+ T cells after heat‐killed sporozoite immunization in mice

Abstract: Malaria remains a major cause of mortality in the world and an efficient vaccine is the best chance of reducing the disease burden. Vaccination strategies for the liver stage of disease that utilise injection of live radiation‐attenuated sporozoites (RAS) confer sterile immunity, which is mediated by CD8+ memory T cells, with liver‐resident memory T cells (TRM) being particularly important. We have previously described a TCR transgenic mouse, termed PbT‐I, where all CD8+ T cells recognize a specific peptide fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…immunogenicity, of SPZ-based vaccines. Our findings extend the work that has previously established the feasibility of improving SPZ immunogenicity via the traditional adjuvanting method of administering a mixture of SPZ and adjuvant ( 27 30 ). Specifically, we found that chemically augmented SPZ-SAS(CL307) can be stably formed and show considerably boosted immunogenicity in vitro , with 35-fold increases in IL-6 production by macrophages compared to unadulterated SPZ.…”
Section: Discussionsupporting
confidence: 87%
“…immunogenicity, of SPZ-based vaccines. Our findings extend the work that has previously established the feasibility of improving SPZ immunogenicity via the traditional adjuvanting method of administering a mixture of SPZ and adjuvant ( 27 30 ). Specifically, we found that chemically augmented SPZ-SAS(CL307) can be stably formed and show considerably boosted immunogenicity in vitro , with 35-fold increases in IL-6 production by macrophages compared to unadulterated SPZ.…”
Section: Discussionsupporting
confidence: 87%
“…A prior study evaluated HK-spz immunization in C57Bl/6 mice previously adoptively transferred with parasite-specific PbT-1 cells. Unadjuvanted HK-spz conferred no sterile protection in such mice, and the addition of a-GalCer protected only one of eight mice, 49 suggesting that viable spz are critical for protection. RAS have limited intrahepatic development but do actively invade hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we asked whether active spz motility in the skin and during liver invasion was critical for protection for ULV ID-RAS + 7DW8-5. Non-motile, heat-killed spz (HK-spz) cannot actively migrate, do not invade hepatocytes, and do not achieve sterile protection against IV-spz challenge in mice 20 , 52 . Similarly, here we found that mice trapped with IV- or ID- HK-spz + / − 7DW8-5 did not provide significant protection against spz challenge (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%